2006
DOI: 10.1364/josaa.23.001631
|View full text |Cite
|
Sign up to set email alerts
|

Scattering of light from quasi-homogeneous sources by quasi-homogeneous media

Abstract: The field generated by scattering of light from a quasi-homogeneous source on a quasi-homogeneous, random medium is investigated. It is found that, within the accuracy of the first-order Born approximation, the far field satisfies two reciprocity relations (sometimes called uncertainty relations). One of them implies that the spectral density (or spectral intensity) is proportional to the convolution of the spectral density of the source and the spatial Fourier transform of the correlation coefficient of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
51
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(52 citation statements)
references
References 12 publications
1
51
0
Order By: Relevance
“…Examples of partially coherent fields include those generated by multimode lasers and beams that have passed through a random medium, e.g., the turbulent atmosphere. Such more general situations have only recently begun to attract attention [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Examples of partially coherent fields include those generated by multimode lasers and beams that have passed through a random medium, e.g., the turbulent atmosphere. Such more general situations have only recently begun to attract attention [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…For example, numerous published articles exist predicting the polarization, coherence, and beam shape of partially coherent light after propagating through free space and random media [1][2][3][4][5][6][7][8][9][10] or scattering from deterministic and random objects/media. [11][12][13][14][15][16][17][18][19][20][21] Much work has also been performed exploiting coherence to control beam shape [22][23][24][25][26][27][28][29][30] and even as an encoding scheme for holography. 31 Excellent reviews and more in-depth discussions of these topics can be found in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Hardly any studies have been devoted to this more general case (see, however, [6]). The extinguished power due to scattering of random fields on a random medium has been analyzed in [7,8], and certain reciprocity relations for cases of this kind were derived in [9]. The extinguished power from scattering a random field on deterministic media was discussed in [10,11].…”
mentioning
confidence: 99%